Self-esteem of youth standing at the threshold of further education or transition to the labour market - on the example of students of lublin secondary schools - Danuta Iwona Wosik-Kawala (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
Self-esteem is one of the factors conditioning the functioning of people in many areas of life, both personal and professional. It influences decisions made by people, including their professional career. The aim of the carried out research was an attempt to determine the self esteem of young people at the threshold of further education or transition to the labour market. 299 students of Lublin schools, including: basic vocational school, technical secondary school and general high school, made a research sample. The Rosenberg Self-Esteem Scale (SES) by Morris Rosenberg was used in the research. Analysis of the data showed that students from various types of schools, standing at the threshold of adulthood do not differ significantly in terms of their self-esteem. Differences were also not noted, taking into account the gender of the people examined. However, the fact that as many as every fourth respondent had a low, unfavourable level of self-esteem turned out to be disturbing. In the case of these students, action should be taken to increase their self-esteem.